Percutaneous Closure of a Patent Ductus Arteriosus in Preterm Infants - Özge Pamukçu; Nazmi Narin (Trends in Pediatrics)
Spontaneous closure rate of ductus decreases as gestational age and birth weight decrease. Therefore, patent ductus arteriosus (PDA) is a very common finding in extremely preterm infants. Most popular questions discussed between neonatologists and pediatric cardiologists are: Whether the ductus is open or not, should we close it or not, when should we close it, and if we have decided to close: should we do it medical, transcatheter or by surgery? In this review we try to clarify patient selection for PDA closure, the main steps of percutaneous PDA closure, device selection, complications, transport, anesthesiology and main trick points in extremely low birth weight infants in the light of our clinical experience and the literature.